A NEW APPROACH FOR LOAD BALANCING IN CLOUD COMPUTING (International Journal of Engineering and Computer Science, 2013)
Cloud computing is built on the base of distributed computing, grid computing and virtualization. The eminence of the place of cloud computing in future converged networks is incontestable. It is due to the obvious advantages of the cloud as a medium of storage with ubiquity of access platforms and minimal hardware requirements on the user end. The scalability, high availability, load balancing, cost, performance are some major issues. Cloud computing environments provide scalability for applications by providing virtualized resources dynamically. Moving applications to a cloud computing environment triggers the need of scheduling as it enables the utilization of various cloud services to facilitate execution. In the proposed algorithm it uses the active monitoring load balancing algorithm and resource aware scheduling algorithm for improved resource utilization and scheduled load balancing for high performance in cloud systems.